2012
DOI: 10.1371/journal.pone.0048245
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Acute Jugular Vein Compression on the Cerebral Blood Flow Velocity, Pial Artery Pulsation and Width of Subarachnoid Space in Humans

Abstract: PurposeThe aim of this study was to assess the effect of acute bilateral jugular vein compression on: (1) pial artery pulsation (cc-TQ); (2) cerebral blood flow velocity (CBFV); (3) peripheral blood pressure; and (4) possible relations between mentioned parameters.MethodsExperiments were performed on a group of 32 healthy 19–30 years old male subjects. cc-TQ and the subarachnoid width (sas-TQ) were measured using near-infrared transillumination/backscattering sounding (NIR-T/BSS), CBFV in the left anterior cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…Authors using cine phase magnetic resonance imaging (MRI) to visualise CSF dynamics in the aqueduct of Sylvius also confirmed earlier report by our group that impaired jugular outflow augments CSF pulsatility [36,37]. This study is in line with Chen et al [8] and Dreha-Kulaczewski et al [9] MRI reports indicating that respiration is one of the major regulators of human CSF flow.…”
Section: Discussionsupporting
confidence: 89%
“…Authors using cine phase magnetic resonance imaging (MRI) to visualise CSF dynamics in the aqueduct of Sylvius also confirmed earlier report by our group that impaired jugular outflow augments CSF pulsatility [36,37]. This study is in line with Chen et al [8] and Dreha-Kulaczewski et al [9] MRI reports indicating that respiration is one of the major regulators of human CSF flow.…”
Section: Discussionsupporting
confidence: 89%
“…The high within- and between-subject reproducibility and repeatability of NIR-T/BSS measurements have been demonstrated previously [10], [12], [13], [16], [32]. NIR-T/BSS, like NIRS, allows for direct within-subject comparisons [16], [35].…”
Section: Discussionmentioning
confidence: 68%
“…In a healthy population, there are no significant differences between hemispheres (i.e. the cc-TQ ratio between the left and right hemispheres was very close to 1.0) [32]. We hypothesized that cc-TQ may serve as a discriminating factor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[3][4][5] IJV compression and engorgement of the cranial venous system enlarges the brain and increases brain turgor (makes stiffer) through changes in vascular dynamics and cerebrospinal fluid (CSF) absorption. 3,[6][7][8][9][10][11] This reduces relative motion, or slosh, between the brain and the skull and diminishes deformation of the brain. Two previous animal studies have shown a striking reduction in axonal injury through pre-injury application of a customized cervical collar introducing IJV compression.…”
Section: Introductionmentioning
confidence: 99%